Validating the antiseizure effects of vitexin and related flavone glycosides in zebrafish - Audrey Breckenridge; Sanskriti Basnyat; Eva Fitch; Colleen Carpenter-Swanson (Frontiers in Pharmacology)
Current epilepsy treatments often fail to provide sufficient control over seizures, highlighting the need for new therapeutic agents. Vitexin, a flavone with antioxidant, anti-inflammatory, and neuroprotective properties, was previously shown to suppress seizure activity in rodent models. Utilizing zebrafish, this study further evaluates the antiseizure properties of vitexin and for the first time, examines the related flavone glycosides: isovitexin, vitexin 2-O-rhamnoside, vitexin-4-O-glucoside and saponarin. We initially tested the ability of the compounds to reduce behavioral seizures stimulated by the GABAA receptor antagonists (pentylenetetrazole: PTZ and picrotoxin: PTX) and spontaneous seizures in a genetic epilepsy model (Dravet syndrome, scn1lab−/− zebrafish larvae). Seizure behavior was quantified in 5-day old larvae via automated tracking with a DanioVision monitoring chamber linked to EthoVision XT 15 software. Microelectrode array electrophysiology (MEA) was then used to examine the effects on PTZ-induced seizure-like brain activity. While having no effect on basal locomotion, vitexin and isovitexin significantly reduced seizure activity in PTZ-treated zebrafish. None of the flavones exhibited antiseizure effects in the PTX-induced epilepsy model. Additional studies with vitexin demonstrated that though it did not suppress spontaneous seizure behaviors in our genetic model of epilepsy, it did significantly inhibit PTZ-induced electrographic activity. These findings support the continued exploration of the translational potential of the vitexin scaffold. This work advances our search for safer, more effective antiseizure drugs and could pave the way for vitexin-based treatments for epilepsy and related disorders.